Understanding the Effect of Emotional Exhaustion on Tellers’ Job Satisfaction in Teller-Task Activity in Ghanaian Retail Banks - Sanda, M.A.; Mawuena, E. (Advances in Intelligent Systems and Computing, 2018)
This study explored the influencing dynamics of tellers’ emotional exhaustion on their job satisfaction necessitated by the increased customer demand of direct teller service in the banking halls, as against the usage of automated teller machines in Ghana. Using a cross-sectional design, quantitative data was collected from five banks with similar institutional arrangements for teller work. Results from factor analysis identified seven factors that are indicative of the tellers’ emotional exhaustion, and four factors that are indicative of their job satisfaction. Results from correlation and regression analyses showed that a rise in the tellers’ emotional exhaustion reduces their satisfaction with the teller job. It is concluded that tellers become emotionally exhausted and dissatisfied with their jobs due to the absence of human resources management mechanisms that could have enabled the efficient design of the teller task and work environments that are conducive with bonded relationships between tellers’ and their supervisors. © Springer International Publishing AG, part of Springer Nature 2019.
Keywords: Emotional exhaustion; Ghana; Job satisfaction; Retail banks; Teller-task activity; Tellers